How Can the Coping Strategies Mediate the Relationship Among COVID-19 Stress, Depression, and Anxiety? - Park, Jeongsoo; Park, Seon Cheol (Psychiatry Investigation, 2024)
Objective The coronavirus disease-2019 (COVID-19) pandemic has had a severe impact on mental health. To explore the underlying mechanisms that influence mental health, a critical question is whether different types of coping strategies may mediate the relationships between COVID-19 related stress and mental health. Methods Recruited between October 19 and 24, 2021, a total of 500 participants aged 20 to 69 years completed an online survey to eval-uate the COVID-19 stress, coping orientation, depression and state anxiety. The period corresponded to the highest level of COVID-19 restrictions (level 4) immediately before the adjusted restriction to level 3. Parallel mediation analyses were conducted using structural equation modeling. Results Distinct mediation effects of the COVID-19 stress (i.e., fear of infection, difficulties of social distancing, anger toward others) through three types of coping strategies (i.e., functional, dysfunctional, seeking support) were found. Fear of infection was likely to be related to functional coping and dysfunctional coping. Social distancing model indicated dysfunctional coping and seeking support, while anger toward others model was associated with functional coping and seeking support. Conclusion The results highlight the different relationships between COVID-19 stress and mental health coping strategies. The identification of these mediation pathways offers guidance for designing effective interventions and support systems to promote psychological well-being during challenging times like the COVID-19 pandemic.
Keywords: Coping strategies; COVID-19; Intervention; Mental health; Stress